2018
DOI: 10.1097/jcn.0000000000000477
|View full text |Cite
|
Sign up to set email alerts
|

User-centered Development of a Decision Aid for Patients Facing Implantable Cardioverter-Defibrillator Replacement

Abstract: Currently, the option of ICD replacement is rarely offered, and patient preferences are seldom elicited. Participants believed the PDA to be a useful intervention that could help facilitate an SDM process for patients facing ICD replacement. Preparing for implementation during the development phase will allow us to strategize effectively to overcome perceived barriers and capitalize on perceived facilitators during actual implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…12 Whereas patient education primarily aims at unilaterally "giving" information, SDM involves more individualized and intentional communication to ensure patients are active participants in decisions about their care. 3 In contrast to the historical view that evidence-based guidelines hold the highest prominence in achieving fully informed consent, SDM ensures that patients are invited to participate in the decision-making process, are adequately informed about the treatment options they face, that their preferences are elicited, and that their priorities are J o u r n a l P r e -p r o o f integrated into treatment recommendations. 4 Where obtaining informed consent is seen as a legal process that ascertains patients' permission to pursue one particular treatment based on the risks provided, SDM invites patients to engage in a conversation about treatment options based on their desired level of involvement, incorporates their preferences, and enables a decision to be made jointly based on the best available evidence.…”
Section: Shared Decision-makingmentioning
confidence: 99%
“…12 Whereas patient education primarily aims at unilaterally "giving" information, SDM involves more individualized and intentional communication to ensure patients are active participants in decisions about their care. 3 In contrast to the historical view that evidence-based guidelines hold the highest prominence in achieving fully informed consent, SDM ensures that patients are invited to participate in the decision-making process, are adequately informed about the treatment options they face, that their preferences are elicited, and that their priorities are J o u r n a l P r e -p r o o f integrated into treatment recommendations. 4 Where obtaining informed consent is seen as a legal process that ascertains patients' permission to pursue one particular treatment based on the risks provided, SDM invites patients to engage in a conversation about treatment options based on their desired level of involvement, incorporates their preferences, and enables a decision to be made jointly based on the best available evidence.…”
Section: Shared Decision-makingmentioning
confidence: 99%
“…Likewise, patients have previously reported not to recall alternatives for committing to ICD therapy ( 41 ). In addition, in a previous study, clinicians have reported that in order to use shared decision making, they needed a hint or trigger from patients, as it was not part of their standard practice ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous endeavors resulted in a healthcare-provider-centered ICD decision aid to be implemented in patients facing an ICD replacement, in order to help healthcare providers step away from the automatism of replacing an ICD at battery depletion instead of discussing the options with their patients first ( 46 ). It is expected from the decision aid resulting from this study, to encourage not only healthcare providers but also patients into taking a more active role in the decision making process prior to the definitive continuation of ICD therapy.…”
Section: Discussionmentioning
confidence: 99%
“…27 For example, the Normalization Process Theory has been used concurrently alongside the Ottawa Decision Support Framework 28 for the development of a PtDA focused on implantable cardiac defibrillator generator replacement. 29…”
Section: Discussionmentioning
confidence: 99%
“…27 For example, the Normalization Process Theory has been used concurrently alongside the Ottawa Decision Support Framework 28 for the development of a PtDA focused on implantable cardiac defibrillator generator replacement. 29 At the PtDA level, newly identified factors were having an up-to-date PtDA available online. However, authors highlighted the lack of funds available following the RCT to update or diffuse the PtDA.…”
Section: Discussionmentioning
confidence: 99%